Status and Prospect of Mushroom Industry in the Philippines - Hyun You Chang; Sung Woo Jeon; Alma Cosadio; Casimero Icalina; Rodel Panganiban; Rosalito Quirino; Yanghoon Song (Philippine Association of Institutions for Research, Inc., 2014)
The mushroom industry in the Philippines has exacerbated since 1995, and the lowest production volume was 355 metric tons (MT) in 2009. Most of the mushroom consumed were imported from the different countries of South East Asia like China, Taiwan, Thailand, Malaysia, Korea and Japan. Growing mushrooms in the Philippines is economically feasible due to low- production cost, abundance of cheap substrates from agro wastes and high demand, which will be profitable to the mushroom growers. The study aimed to assess the production of mushroom in some parts of the Philippines, assess their potentials and introduce the non-sterile fermentation method of growing mushroom to the Philippine mushroom industry. There are ten varieties of edible and medicinal mushrooms grown in the Philippines such as Paddy straw mushroom, Oyster mushroom, Shiitake mushroom, Button mushroom, Ear fungi mushroom, Milky mushroom, Yellowish oyster mushroom, Reishi mushroom, Lion`'s mane mushroom, and  King tuber oyster mushroom. Supporting the mushroom industry is vital in developing the rural economy, enhancing employment and income opportunity in the rural communities as well as providing income to the small farmers.